The Conduct of War 1789-1961 - Fuller, J. F. C. (GHQ, Rawalpindi Services Book Club, 1986)
A study of the impact of the French, industrial, and Russian revolutions on war and its conduct.
Include Appendices and Index.
Keywords: Military art and science -- Military history, Modern -- War and society -- Europe